Changing trends in crop management practices and performance attributes of rice-based systems of coastal Bangladesh - Islam, Md Amirul; Pariyar, Shyam; Krupnik, Timothy J.; Becker, Mathias (Frontiers in Agronomy, 2024)
Climate change affects changes in rice-based systems of coastal Bangladesh. Both external pressures and system-immanent attributes influence farmers’ adoption of new production practices, leading to the emergence of new land use patterns. Field and household surveys quantified recent and emerging change trends in crop yields and associated intensification-related practices in representative rice-based systems, using a diachronic approach (comparing the years 2011 and 2021). We analyzed 240 rice-producing farms, representing three rice-based cropping systems, namely extensive rice-fallow rotations, intensified irrigated rice double rotations, and diversified rice-mungbean rotations. The study sites contrasted favorable biophysical conditions (climate, soil type, water source and quality, soil fertility) in the Barishal district, and marginal (unfavorable biophysical environments) conditions at Patuakhali district in coastal Bangladesh. Soil fertility attributes were assessed at both study sites. The type, the extent, and the pathways of recent changes differed between locations, systems and seasons. We observed significant increases in aggregated yield (across crops and seasons), in individual crop yields, and in economic yields at both the marginal and the favorable sites. Crop yields varied widely (rice: 3.0–7.8 t ha–1, mungbean: 0.4–1.5 t ha–1), and rice yield was higher in dry than in the wet season. Farmers’ adoption of intensification practices started earlier in the marginal study area, but the extent of the changes was larger at favorable sites. Most prominent was the mechanization of tillage operations and an increased use of mineral fertilizers, with the largest changes observed in irrigated rice and in dry season mungbean. Such site-, system-, and season-specific assessments will permit identifying drivers of change and can inform the assessment of potential future patterns of land system changes.